Effects of fiber orientation on tool wear evolution and wear mechanism when cutting carbon fiber reinforced plastics - Wu, Weizhou; Li, Shipeng; Qin, Xuda; Liu, Wentao; Cui, Xin; Li, Hao; Shi, Mengrui; Liu, Haibao (Elsevier, 2023)
The aim of the present paper is to reveal the influence of different fiber orientations on the tool wear evolution and wear mechanism. Side-milling experiments with large-diameter milling tools are conducted. A finite element (FE) cutting model of carbon fiber reinforced plastics (CFRP) is established to get insight into the cutting stress status at different wear stages. The results show that different fiber orientations bring about distinct differences in the extent, profile and mechanism of tool wear. Severer wear occurs when cutting 45° and 90° plies, followed by 0°, correspondingly, the least wear is obtained when θ = 135° (θ represents the orientation of fibers). Moreover, the worn profiles of cutting tools when θ = 0° and 45° are waterfall edge, while round edge occurs when θ = 135° and a combined shape of waterfall and round edge is obtained when θ = 90°. The wear mechanisms under different fiber orientations are strongly dependent on the cutting stress distributions. The evolution of tool wear profile is basically consistent with the stress distribution on the tool surface at different wear stages, and the extent of tool wear is determined by the magnitude of stress on the tool surface. Besides, the worn edges produce an actual negative clearance angle, which decreases the actual cutting thickness and leads to compressing and bending failure of fibers beneath the cutting region as well as low surface qualities.
Keywords: carbon fiber reinforced plastics (CFRP); fiber orientation; finite element method (FEM); tool wear; wear mechanism